Maintenance Web Based Applications Using Feature Location - Arwan, Achmad; Rusdianto, Denny Sagita (Faculty of Computer Science (FILKOM) Brawijaya University, 2020)
Maintenance web applications are a complex set of efforts. The FilkomApps are the web application used by the Faculty of Computer Science of Universitas Brawijaya to arrange the academic, theses of students, assignment of faculty, inventory, presence, honorarium. It has about 6K number of files(HTML, PHP, JS, CSS). The feature location was able to help the maintenance of the web applications by locating specific features on the files. The process comprises of preprocessing (tokenizing, web language syntax removal, splitting, stopword and stemming), indexing (VSM Lucene), and evaluations (precision and recall). The experiments were done by querying the keywords originate from previous maintenance modification effort and feature of a system. The results of precision were 86% and recall were 47%. The precision was better 374% than the conventional method (using the IDE search feature)